Transboundary water interaction III: contest and compliance - Zeitoun, M.; Cascao, A.E.; Warner, J.; Mirumachi, N.; Matthews, Nathaniel (Springer, 2017)
This paper serves international water con ict resolution efforts by examining the ways that states contest hegemonic transboundary water arrangements. The conceptual framework of dynamic transboundary water interaction that it presents integrates theories about change and counter-hegemony to ascertain coercive, leverage, and liberating mechanisms through which contest and transformation of an arrangement occur. While the mechanisms can be active through sociopolitical processes either of compliance or of contest of the arrangement, most transboundary water interaction is found to contain elements of both. The role of power asymmetry is interpreted through classi cation of intervention strategies that seek to either in uence or challenge the arrangements. Coexisting contest and compliance serve to explain in part the stasis on the Jordan and Ganges rivers (where the non-hegemons have in effect consented to the arrangement), as well as the changes on the Tigris and Mekong rivers, and even more rapid changes on the Amu Darya and Nile rivers (where the non-hegemons have confronted power asymmetry through in uence and challenge). The framework also stresses how transboundary water events that may appear isolated are more accurately read within the many sociopolitical processes and arrangements they are shaped by. By clarifying the typically murky dynamics of interstate relations over transboundary waters, furthermore, the framework exposes a new suite of entry points for hydro-diplomatic initiatives.